Questions & Answers : New Materialism, Old Media - Hofer, Kristina Pia; Stockburger, Axel (My University, 2017)
Im this dialog, Axel Stockburger and Kristina Pia Hofer discuss how objects as subjects to changes by way of discoursive shifts may shift their weight, and how queer_feminist discourses on materialism intersect with those in contemporary art markets.
Keywords: 700 Künste, Bildende und angewandte Kunst